Change of Pronation Angle of the Subtalar Joint has Inluence on Plantar Pressure Distribution - João Otacilio Libardoni dos Santos; Eliane Fátima Manfio; Felipe Pivetta Carpes; Ewertton de Souza Bezerra; Rudnei Palhano; Aluisio Otavio Vargas Avila (Universidade Federal de Santa Catarina, 2017)
Several studies have investigated the relationship between heel pronation with plantar pressure during gait. With a degree of variability and inluence of the footwear, usually excessive pronation is associated with higher mechanical loads. However, larger loads are commonly associated with pronation. his study aims to compare the plantar pressure distribution among individuals with diferent pronation angles of the subtalar joint angle during gait with controlled speed. he maximum angle of the subtalar joint was determined by capturing images in the frontal plane and the pressure plant peaks were acquired by EMED pressure platform. he pronated group showed pressure plant peaks signiicantly higher in the lateral heel area (18%; p=0.031), medial heel (17%, p=0.034), lateral midfoot (30%; p=0.032) and medial midfoot (41%; p=0.018) when compared to the control group. Excessive pronation of the subtalar joint caused changes in plantar pressure distribution, and an increase in pressure plant peaks, especially in the heel and midfoot regions. his demonstrates the need for a speciic care of this population, mainly because the increased pressure plant peaks is related to pain in the feet and onset of injuries.